2011
DOI: 10.1007/s13105-011-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nuclear-encoded genes involved in mitochondrial biogenesis and dynamics in experimentally denervated muscle

Abstract: The abundance, morphology, and functional properties of mitochondria become altered in response to denervation. To gain insight into the regulation of this process, mitochondrial enzyme activities and gene expression involved in mitochondrial biogenesis and dynamics in mouse gastrocnemius muscle was investigated. Sciatic nerve transactions were performed on mice, and then gastrocnemius muscles were isolated at days 5 and 30 after surgery. Muscle weight was decreased significantly by 15% and 62% at days 5 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 70 publications
4
22
1
Order By: Relevance
“…In addition, we observed that unloading significantly decreased mRNA expression levels of Tfam and ERR-␣, which is in line with data from Wagatsuma et al who reported decreased expression levels of these regulators in soleus muscle of hindlimb-suspended rats (45). Interestingly, decreased expression levels of PGC-1 molecules and ERR-␣ are also observed in other models of disuse-induced loss of muscle OXPHEN such as denervation and spaceflight-induced gravitational unloading, suggesting that disuse of the musculature in broad terms initiates a conserved transcriptional program that leads to a coordinated downregulation of muscle OXPHEN (1,35,46). Although the focus of this study was not to investigate the impact of disuse on muscle OXPHEN and its molecular regulation, we identified that only a subset of the regulators we investigated shows decreased expression levels upon unloading (PGC-1␤, Tfam, and ERR-␣), whereas the mRNA abundance of other regulatory molecules such as NRF-1, NRF-2␣, PPAR-␦, and SIRT-1 remained unaltered.…”
Section: E619 Alternative Nf-b Signaling During Recovery Of Muscle Oxsupporting
confidence: 90%
“…In addition, we observed that unloading significantly decreased mRNA expression levels of Tfam and ERR-␣, which is in line with data from Wagatsuma et al who reported decreased expression levels of these regulators in soleus muscle of hindlimb-suspended rats (45). Interestingly, decreased expression levels of PGC-1 molecules and ERR-␣ are also observed in other models of disuse-induced loss of muscle OXPHEN such as denervation and spaceflight-induced gravitational unloading, suggesting that disuse of the musculature in broad terms initiates a conserved transcriptional program that leads to a coordinated downregulation of muscle OXPHEN (1,35,46). Although the focus of this study was not to investigate the impact of disuse on muscle OXPHEN and its molecular regulation, we identified that only a subset of the regulators we investigated shows decreased expression levels upon unloading (PGC-1␤, Tfam, and ERR-␣), whereas the mRNA abundance of other regulatory molecules such as NRF-1, NRF-2␣, PPAR-␦, and SIRT-1 remained unaltered.…”
Section: E619 Alternative Nf-b Signaling During Recovery Of Muscle Oxsupporting
confidence: 90%
“…In muscle taken within 10 days from children with severe burn injury, downregulated mitochondrial biogenesis has been suggested (723). In experimentally denervated gastrocnemius muscle of rats and mice (a model of disuse), strong reductions in mitochondrial content coincided with a remarkable downregulation of several key players of mitochondrial biogenesis several weeks after the insult (5,750). Several components of the mitochondrial biogenesis pathway appeared downregulated at gene expression level after 24 h of endotoxemia, which was more pronounced in mouse tibialis anterior and soleus muscle than in diaphragm (490).…”
Section: Mitochondrial Biogenesis In Critical Illnessmentioning
confidence: 99%
“…In the experimental model of sciatic nerve transection, Lon protease was down-regulated at day 30 after surgery, which correlated with a decreased number of functional mitochondria [83]. …”
Section: Lon Involvement In Human Diseasesmentioning
confidence: 99%